Analisis Mutu Sensori, Cemaran Mikroba Escherichia Coli dan Cemaran Logam Timbal (Pb) pada Cumi-cumi (Loligo Sp) Beku di Queen Seafood Pasuruan - Ahmad Azkal Azkiya; Illyatu Sholiha (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the sensory quality, Escherichia coli microbial contamination, and lead (Pb) content in frozen squid (Loligo sp) produced by Queen Seafood in Pasuruan. The method used is descriptive qualitative with laboratory testing of whole frozen squid samples. The testing includes sensory evaluation (ice layer, appearance, aroma, and texture), microbiological testing to detect the presence of E. coli using the APM method, and lead (Pb) contamination testing using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that all sensory quality parameters of frozen squid met the SNI 9192:2023 standard with an average score above the minimum limit. However, Escherichia coli contamination exceeded the maximum threshold set in the SNI, which is suspected to originate from unclean production water sources. The lead (Pb) content was recorded at 0.075 mg/kg, which is still within the safe limit according to the SNI (<1.0 mg/kg). These findings emphasize the importance of water quality monitoring in the production process and the need for additional washing and reprocessing instructions before consumption to ensure the food safety of frozen squid.